KEBIJAKAN AFFIRMATIVE ACTION PADA SELEKSICALON PEGAWAI NEGERI SIPILTAHUN 2018 DI KABUPATEN BANJAR - LOLA MALIHAH (Institut Agama Islam Darussalam Martapura, 2019)
AbstractIn human resource management, workforce diversity is very influential on employment opportunities, so some groups not getting the same job opportunities. For this reason, it is important for the government to present an affirmative action policy as a means of providing equal opportunities to these groups by giving special treatment. What makes it interesting is that in 2018 the government issued a new policy on the affirmative action system, namely by adding formations from five to six. However, in a study conducted in Banjar Regency, South Kalimantan, only one formation was available from the six special formations determined by the central government. It is because in the selection of prospective civil servants in Banjar District, general and special formations are only provided for teaching staff. This research was conducted with the aim to find out the application of the affirmative action policy on the selection of prospective civil servants in 2018 in Banjar Regency, which raises a sense of curiosity towards the realization of the implementation of the existing affirmative action policy.The research method was conducted in the form of descriptive analytic, by applying secondary data types obtained from documents in the Banjar Regency Regional Personnel Agency, literature study, and direct interviews with the Regional Personnel Agency.Keywords: affirmative action policy, Banjar Regency, selection of prospective civil servants.